A Novel Flexible Green Composite with Sisal and Natural Rubber: Investigation under Low-Velocity Impact. Issue 15 (23rd November 2022) - Rajkumar, Dasari; Mahesh, Vishwas; Joladarashi, Sharnappa; Kulkarni, Satyabodh M
ABSTRACT: The present work concentrates on assessing the low-velocity impact (LVI) response of sisal-natural rubber (NR)-based flexible green composite in two different stacking sequences, namely, sisal/rubber/sisal (SRS) and sisal/rubber/sisal/rubber/sisal (SRSRS). The influence of the impactor shape on LVI response of the proposed composite was assessed using hemispherical and conical-shaped impactors. Results showed that the proposed composites exhibit better energy absorption and resistance to damage due to inclusion of compliant matrix. The study of damage mechanism of the proposed composites showed that the inclusion of NR as a matrix material in the proposed composites helps to avoid catastrophic failure since rubber undergoes failure by matrix tearing as opposed to matrix cracking as in the case of stiff composites. The proposed composites eliminate two of the major damage mechanisms, namely, matrix cracking and delamination, due to usage of compliant matrix material. The results obtained suggest that the proposed flexible composites can serve as excellent sacrificial structures. The outcome of the present study serves as a benchmark for interested designers/engineers to explore the usage of natural material candidates for developing sustainable impact-resistant composites.